Randomized controlled trial of Functional Family Therapy for offending and antisocial behavior in UK youth. (15th May 2017) - Humayun, Sajid; Herlitz, Lauren; Chesnokov, Melanie; Doolan, Moira; Landau, Sabine; Scott, Stephen
Abstract : Background: Youth offending and antisocial behavior (ASB) are associated with low quality mental health and relationships and usually lead to poor adult functioning; they are very costly for society. Family interventions are effective in children but there are few reliably effective and inexpensive interventions for adolescents. Functional Family Therapy (FFT) is an evidence‐based intervention but seldom tested outside the United States. Methods: One hundred and eleven adolescents (10–17 years of age, M  = 15.0, SD  = 1.63) and their families were randomized to FFT + Management As Usual (MAU) ( n  = 65) or to MAU ( n  = 46). Assessments were made at baseline 6, and 18 months after randomization and included interviews and questionnaires of parenting behaviors, conduct disorders (CDs) and offending. Parent–child interaction was directly observed and police records obtained. Trial registration: ISRCTN27650478. Results: Eighty‐nine (80%) were followed‐up. In both groups, there were large reductions over time in all measures of offending and antisocial behavior (e.g. primary outcome p  <   0.001), but no significant changes over time in parenting behavior or the parent–child relationship. However, there were no differences between intervention and control groups at 6 or 18 months on self‐reported delinquency, police records of offending, symptoms or diagnoses of CDs, parental monitoring or supervision, directly observed child negative behavior, or parental positive or negative behavior. Against predictions, the intervention group showed lower levels of directly observed child positive behavior at 18 months compared to controls. Conclusions: In contrast to most previous trials of FFT, FFT+MAU did not lead to greater reductions in youth ASB and offending compared to MAU alone, and did not lead to improvements in parenting or the parent–child relationship. This may be because the trial was more rigorously conducted than prior studies; equally, the possibility that MAU was effective requires further research.